COMPARISON OF FUNCTIONAL OUTCOME BETWEEN CONSERVATIVE AND SURGICAL TREATMENT FOLLOWING FINGERTIP INJURY IN ADULT– A 3-MONTH LONGITUDINAL STUDY - Zulkifly, Mohd Firdaus; Khalid, Kamarul Ariffin (International Journal of Allied Health Sciences, 2021)
Finger injury is the most common upper extremity injury and is commonly work related. Poor functional outcome following the injury is associated with financial burden mainly due to work limitation. The objective of this study is to measure functional outcome following fingertip injuries in a public tertiary hospital in Negeri Sembilan. A 3-month prospective longitudinal study was conducted involving 57 respondents from the orthopaedic clinic from May 2018 until May 2019. The functional outcomes from the fingertip injury were measured using the Michigan Hand Outcomes Questionnaire (MHQ), range of motion, and two-point discrimination test. The study recorded a 97.1% response rate. The mean MHQ score showed a significant improvement in a scale of 1 to 100 on the functional outcome with 49.35 (±11.79) and 58.54 (±10.95) at 1 and 3 months, respectively. The range of motion and two-point discrimination test also showed a significant improvement at 3 months post-injury. This study also found surgical treatment recorded lower functional outcome compared to conservative treatment at both 1- and 3-month postinjury. In conclusion, the functional outcomes of fingertip injury in public tertiary hospital recorded a satisfying level. However, lower outcomes were observed with surgical treatment that could be due to the complexity of the patient’s injury